2022
DOI: 10.2147/amep.s374133
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction and Self-Efficacy in a Novel Online Clinical Clerkship Curriculum Delivered During the COVID-19 Pandemic

Abstract: Purpose The COVID-19 pandemic has caused significant disruption to medical education and clinical training and resulted in stressors that impede student learning. This study aimed to assess student satisfaction and self-efficacy in a novel online clinical clerkship curriculum delivered during the COVID-19 pandemic. Methods Fourth- and fifth-year medical students completed an online survey in January 2021 covering the following areas: student satisfaction, self-efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Utilizing information technology can also facilitate the learning process for the medical profession study program [15]- [17]. Especially during the coronavirus disease (COVID-19) pandemic, a lot of research has been conducted to evaluate the novel learning process by using information technology [18]- [20]. Quality progress in the learning process must result in positive changes, such as motivated students who actively engage in the learning process and achieve excellent learning outcomes [21].…”
Section: Issn: 2088-8708 mentioning
confidence: 99%
“…Utilizing information technology can also facilitate the learning process for the medical profession study program [15]- [17]. Especially during the coronavirus disease (COVID-19) pandemic, a lot of research has been conducted to evaluate the novel learning process by using information technology [18]- [20]. Quality progress in the learning process must result in positive changes, such as motivated students who actively engage in the learning process and achieve excellent learning outcomes [21].…”
Section: Issn: 2088-8708 mentioning
confidence: 99%
“…20 There is also a paucity of published data on self-efficacy in the context of medical education in the Caribbean setting. 13 , 53 , 54 A recent study in a Barbadian medical school evaluated medical student satisfaction and self-efficacy as they participated in a novel online clinical clerkship curriculum which was delivered during the COVID-19 pandemic. The authors reported that although students’ general acceptance of the online curriculum was low, they reported relatively higher levels of satisfaction and perceived self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The satisfaction with online learning in medical students is based on specific community, educational, social, cultural, and economic differences [ 13 ]. The overall results highlight a moderate individual satisfaction and a low perception of effectiveness [ 14 , 15 ]; however, learning outcomes based on academic results, building skills, and interactivity remain unclear [ 16 ].…”
Section: Introductionmentioning
confidence: 99%